Mind the Gap - Jane Hall; Giles Smith (Oz, 2012)
Assemble is a young practice with a background in a range of disciplines: architecture, film, electrical engineering, carpentry, and stone carving, to name just a few. Our first project, the Cineroleum, turned a roadside site into a cinema while our second, Folly for a Flyover, was more ambitious, bringing activity to a space below a motorway on the Olympic fringe.